Peningkatan Kompetensi Guru Madrasah Ibtidayah Duren dan Sabilul Huda Bandungan melalui Pelatihan Pembelajaran Berbasis Teknologi Informasi - Ahmad Ilham; Akhmad Fathurrohman; Muhammad Sam'an; Safuan Safuan; Muhammad Munsarif; Luqman Assaffat; Asdani Kindarto; Arfido Ramadhani; Juyus Muhammad Adinullhaq; Febrianto Febrianto; Irvan Nurmantoro; Yevi Alviatul Ardhani; Nova Ariyanto (Universitas Muhammadiyah Semarang, 2023)
Madrasah Ibtidaiyah (MI) Duren Village and Sabilul Huda Jimbaran Bandungan District Semarang Regency want to produce quality graduates. However, the competence of teachers is still conventional learning aids so the learning process is not optimal. To answer this problem, the Department of Informatics, Faculty of Engineering at Universitas Muhammadiyah Semarang, Indonesia proposed information technology-based learning training activities for madrasah teachers. The purpose program is to strengthen human resources for teachers in MI Desa Duren and Sabilul Huda Jimbaran. The proposed program is divided into three learning schemes, (1) interactive presentation media, (2) online classroom learning, and (3) online learning evaluation. The results of this program are that the participants proved to be able to produce effective, elaborative, and interactive teaching materials based on information technology so that students are not bored and enthusiastic about following lessons in the classroom. It can be cancluded the program with the theme